Positively charged polysilsesquioxane/iodide lonic liquid as a quasi solid-state redox electrolyte for dye-sensitized photo electrochemical cells: infrared, 29 Si NMR, and electrical studies (International Journal of Photoenergy)
A new sol-gel precursor based on 1-methyl-3-[3-(trimethoxy- λ 4 -silyl)propyl]-1 H -imidazolium iodide (MTMSPI + I − ) was synthesized and investigated as a potential novel quasi solid-state ionic liquid redox electrolyte for dye-synthesized photoelectrochemical (DSPEC) cells of the Graetzel type. MTMSPI + I − was hydrolyzed with acidified water and the reaction products of the sol-gel condensation reactions assessed with the help of 29 Si NMR and infrared spectroscopic techniques. Results of the time-dependent spectra analyses showed the formation of positively charged polyhedral cube-like silsesquioxane species that still contained a small amount of silanol end groups, which were removed after heating at 200 ° C . After cooling, the resulting material formed is a tough, yellowish, and transparent solid, which could be reheated again and used for assembling DSPEC cells. The addition of iodine increased the specific conductivity of the hydrolyzed and nonhydrolyzed MTMSPI + I − , which we attributed to the formation of triiodide ions contributed to the conductivity via the Grotthus mechanism. DSPEC cells based on a titania-dye system with MTMSPI + I − electrolyte containing iodine (0.1 M) reached an overall efficiency between 3.3–3.7%.